Development of different degrees of elastase-induced emphysema in mice: a randomized controlled experimental studyenfisema pulmonar, mecânica pulmonar, elastase pancreática. - Palma Kuhl, Cristiana; Alves Garcez, Tuane Nerissa; Bileski Magrisso, Alessandra; Fernandes Correia Laurino, Claudia Cilene; Obino Cirne-Lima, Elizabeth; Rieken Macedo Rocco, Patricia; Vieira de Macedo Neto, Amarilio (Clinical and Biomedical Research, 2014)
Introduction: Mouse models of emphysema are important tools for testing different therapeutic strategies. The aim of this study was to develop a mouse model of emphysema induced by different doses of elastase in order to produce different degrees of severity. Methods: Thirty female mice (C57BL/6) were used in this study. Different doses of porcine pancreatic elastase were administered intratracheally once a week for four weeks, as follows: 0.1 U (n=8), 0.15 U (n=7), and 0.2 U (n=7). Control mice (n=8) received 50 microL of sterile saline solution intratracheally. Lung mechanics were analyzed by plethysmography. Mean linear intercept and volume fraction occupied by collagen and elastic fibers were determined. Results: An increase in lung resistance was observed with 0.2 U of elastase [median (P-25-P75): 2.02 (1.67; 2.34) cmH2O.s/mL], as well as a decrease in tidal volume and minute ventilation. Peak expiratory flow increased significantly in the groups treated with 0.15 U and 0.2 U of elastase. Mean linear intercept was higher with 0.15 U and 0.2 U of elastase, with destruction of alveolar walls [median (P-25-P75): 30.31 (26.65-43.13) microm and 49.49 (31.67-57.71) microm respectively]. The volume fraction occupied by collagen and elastic fibers was lower in the group receiving 0.2 U of elastase. Conclusion: Four intratracheal instillations of 0.2 U of elastase once a week induced changes in lung function and histology, producing an experimental model of severe pulmonary emphysema, whereas 0.15 U resulted in only histological changes.